2016
DOI: 10.1016/j.jnucmat.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

MeV per nucleon ion irradiation of nuclear materials with high energy synchrotron X-ray characterization

Abstract: The combination of MeV/Nucleon ion irradiation (e.g. 133 MeV Xe) and high energy synchrotron x-ray characterization (e.g. at the Argonne Advanced Photon Source, APS) provides a powerful characterization method to understand radiation effects and to rapidly screen materials for the nuclear reactor environment. Ions in this energy range penetrate ~ 10µm into materials. Over this range, the physical interactions vary (electronic stopping, nuclear stopping and added interstitials). Spatially specific x-ray (and TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To examine the amorphization behavior of U 3 Si 2 at high irradiation dose that corresponds to the typical LWR cycle length, in-pile irradiation (e.g. ATF-1 campaign) or high-energy ex situ ion irradiation experiments [18,19] are necessary. It was observed that at these elevated temperatures (350 • C and 550 • C), nanoscale crystalline domains start to form within the TEM foils at the beginning of ion irradiation (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the amorphization behavior of U 3 Si 2 at high irradiation dose that corresponds to the typical LWR cycle length, in-pile irradiation (e.g. ATF-1 campaign) or high-energy ex situ ion irradiation experiments [18,19] are necessary. It was observed that at these elevated temperatures (350 • C and 550 • C), nanoscale crystalline domains start to form within the TEM foils at the beginning of ion irradiation (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, UC1-xNx fuel kernels used has a diameter of ~810 microns. The swift ion irradiation was conducted at the Argonne Tandem Linac Accelerator System (ATLAS) at Argonne National Laboratory [1,2]. Four UC1-xNx fuel kernels were mounted on each of three separate sample stages made of oxygen-free high conductive (OFHC) copper using PELCO high conductivity silver paste.…”
Section: Samples and Swift Ion Irradiationmentioning
confidence: 99%
“…In order to produce irradiated specimens with a welldefined radiation dose, mechanically polished U-10Mo monolithic discs were directly utilized in this study. The swift ion irradiation was conducted at Argonne Tandem Linac Accelerator System (ATLAS) at Argonne National Laboratory [1,2]. Three individual U-10Mo monolithic discs were mounted on each of three separate sample stages made out of oxygen-free high conductive (OFHC) copper using PELCO high conductivity silver paste.…”
Section: Samples and Swift Ion Irradiationmentioning
confidence: 99%